2015
DOI: 10.1016/j.jcf.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health-related quality of life among children with cystic fibrosis and their parents in two Eastern European countries

Abstract: Observed differences in evaluation of HRQOL may be caused by different therapeutic and diagnostic challenges between countries. To identify possible presence of psychosocial problems, monitoring of HRQOL is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…In this study, school attendance of the patients was found as an important factor affecting several fields of the QoL. Borawska-Kowalczyk et al found the same results in their study (21). CF children have many absences from school due to frequent visits to the CF center, hospitalizations or parental refuse because of complications like sleepless nights due to cough or abdominal pain or protection against many infections among peers at school.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this study, school attendance of the patients was found as an important factor affecting several fields of the QoL. Borawska-Kowalczyk et al found the same results in their study (21). CF children have many absences from school due to frequent visits to the CF center, hospitalizations or parental refuse because of complications like sleepless nights due to cough or abdominal pain or protection against many infections among peers at school.…”
Section: Discussionsupporting
confidence: 68%
“…The predicted FEV1 estimates were significantly associated with emotion and school functioning domains. Borawska-Kowalczyk et al identified a significant correlation between QoL and disease severity (21). No correlation was found between the change in Healthrelated QoL (HRQoL) and FEV1 change in the study by van Horck et al (20).…”
Section: Discussionmentioning
confidence: 94%
“…Além do tempo, os aspectos econômicos familiares e o sistema de saúde pelo qual é realizado o tratamento influenciam a QV (BORAWSKA-KOWALCZYK;SANDS, 2015;CHEVREUL et al, 2015). Estes aspectos foram confirmados no estudo de Borawska-Kowalczyk e Sands (2015) que encontraram sobrecarga maior dos pais e das crianças polonesas quando comparadas com as húngaras, fato explicado pelo melhor e maior suporte financeiro neste último país.…”
Section: Discussionunclassified
“…In children and adolescents with CF, hopelessness about future, stigmatization perception, and school absenteeism have been related to an impaired quality of life. 8,19,20 In these CF patients whose life expectancy has been prolonged, determining psychosocial factors affecting quality of life may bring about psychosocial interventions. As to the best of our knowledge, this study is the first to examine the relationship between psychiatric disorders diagnosed by a structured psychiatric interview and QOL in children and adolescents with CF.…”
Section: Cystic Fibrosis (Cf) Is a Genetic Disorder With Autosomal Rementioning
confidence: 99%